Infrastructure Development and Regional Economic Growth: Evidence from the Trans Sumatra Toll Road in Lampung Province - Juliater Simamora; Euis Saribanon; Okin Ringan Purba; Harry Purwoko; Haris Haris (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study examines the impact of the Trans Sumatra Toll Road on regional economic growth and local government revenue in Lampung Province, Indonesia. Using panel data from six districts for the period 2013–2022, this research employs a quantitative approach to analyze the relationships among transportation and warehousing, tourism, agriculture–forestry–fisheries sectors, local government revenue, and economic growth. The empirical results indicate that transportation and warehousing significantly and positively influence both local government revenue and regional economic growth, while local government revenue also exhibits a significant positive effect on economic growth. Conversely, tourism and agriculture–forestry–fisheries sectors do not show a significant direct impact on economic growth, although tourism contributes significantly to local government revenue. Furthermore, transportation and warehousing indirectly affect economic growth through local government revenue, highlighting the mediating role of fiscal capacity in infrastructure-led development. These findings suggest that transportation infrastructure plays a crucial role in enhancing regional economic performance and fiscal capacity, whereas sectoral diversification and value-added strategies are required to strengthen the contributions of tourism and primary sectors. The study provides policy implications for regional governments in optimizing infrastructure investment to foster sustainable regional development.   Keywords: Transportation Infrastructure, Local Government Revenue, Economic Growth, Regional Development, Panel Data